1979
DOI: 10.1093/rheumatology/18.3.167
|View full text |Cite
|
Sign up to set email alerts
|

Joint Laxity Leading to Osteoarthrosis

Abstract: Joint laxity was compared in 50 females with symptomatic osteoarthrosis and an age-matched control group without osteoarthrosis. Generalized joint laxity measured by the scoring system of Cater and Wilkinson (1964) modified by Beighton (1973) was significantly higher in the osteoarthritic group (X2 = 10.00, P less than 0.05). In osteoarthritics the pattern of clinical joint involvement varied with the degree of generalized joint laxity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
1

Year Published

1987
1987
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(27 citation statements)
references
References 0 publications
0
25
1
Order By: Relevance
“…Community studies have confirmed a positive association between knee OA and chondrocalcinosis 14. There is an increased incidence of calcium pyrophosphate dihydrate and basic calcium phosphate crystals in synovial fluid and cartilage from OA joints,15 and also local mechanical factors (including joint hypermobility16 and instability,17 joint motion,18 ligamentous laxity19 and joint damage from surgery20 21 and trauma22) are known to predispose to localised secondary deposition of calcium pyrophosphate dihydrate crystals in the context of joint damage. It is possible that OA results in changes in tissue factors, either an increase in promoters or a reduction in inhibitors of crystal nucleation and growth, which might predispose not just to calcium crystal but also to MSU crystal deposition.…”
Section: Discussionmentioning
confidence: 98%
“…Community studies have confirmed a positive association between knee OA and chondrocalcinosis 14. There is an increased incidence of calcium pyrophosphate dihydrate and basic calcium phosphate crystals in synovial fluid and cartilage from OA joints,15 and also local mechanical factors (including joint hypermobility16 and instability,17 joint motion,18 ligamentous laxity19 and joint damage from surgery20 21 and trauma22) are known to predispose to localised secondary deposition of calcium pyrophosphate dihydrate crystals in the context of joint damage. It is possible that OA results in changes in tissue factors, either an increase in promoters or a reduction in inhibitors of crystal nucleation and growth, which might predispose not just to calcium crystal but also to MSU crystal deposition.…”
Section: Discussionmentioning
confidence: 98%
“…8,49,52 Some authors 6,51 reported that up to 60% of individuals with HMS developed osteoarthritis (OA) as opposed to 30% of patients without HMS who were seen in a rheumatology clinic. Other researchers 53 found that 24% of patients with OA had HMS, as opposed to only 8% of patients seen for general medical conditions. An increased incidence of OA may be secondary to chronic or traumatic biomechanical abnormalities or proprioceptive deficits.…”
Section: Clinical Presentationmentioning
confidence: 90%
“…Alterations or a shift in AP translational and IE rotational motion (Blankenvoort et al, 1988) of the knee during dynamic activities could have profound effects on secondary restraints such as the medial meniscus. Clinical reports (Buckland-Wright et al, 2000;Daniel et al, 1994;Lohmander and Roos, 1994;Roos et al, 1995;Scott et al, 1979) of the presence of osteoarthritis of the knee in patients with ACL injury suggest that abnormal motion at the knee could be a cause of degenerative changes. Yet, increased passive clinical laxity based on quantitative measurement has not correlated with clinical outcome (Snyder Mackler et al, 1997).…”
Section: Introductionmentioning
confidence: 99%